Potency of Cassava Starch (Amylum Manihot) With a Combination of Gelling Agent Methyl as a Moisturizer Product Preparation - Yahya Febrianto; Desy Suweni Nugrahaningtyas (Experimental Student Experiences, 2024)
This study aims to evaluate whether cassava starch can be used as a basic ingredient in moisturizing gel formulations and to determine the effect of various thickening agents on the evaluation and physical stability of moisturizing gel preparations. This research was conducted experimentally. In this study, cassava starch was extracted using water as a solvent. Several variations of thickening agents were used, namely Methylcellulose with concentrations of 6%, 5%, 4%, 3%, and 2%, and CMC Na with concentrations of 2%, 3%, 4%, 5%, and 6%. The physical test results showed that all moisturizing gel formulations (formula 1, 2, 3, 4, and 5) had a semi-solid form with a thick consistency. This preparation has a characteristic odor, is colorless, and gives a cooling sensation when applied to the skin. The results of the spreadability test showed a range of values between 8.90 to 25.70 cm2. The results of the stickiness test show a range of values between 38.20 to 47.44 seconds. While the results of pH measurements of the preparations showed a range of values between 5.70 to 6.65. Statistical analysis using the ANOVA test for spreadability, adhesion, and pH showed that there were significant differences between each formula (p <0.05).